Hubungan penerapan family centered care oleh perawat dengan stres orangtua selama hospitalisasi bayi - Sarjiyah Sarjiyah; Endar Timiyatun; Sri Hariyanti (STIKes Surya Global Yogyakarta, 2018)
Hospitalization of infant causes stress of the parents. Stress which is experienced by parents during infant’s hospitalization has a negative impact. Some of the effects of parental stress include physical problems (fatigue, insomnia, gastritis, headaches, anorexia), and psychosocial problems (frustration, depression, self-blame, emotional and uncooperative) One of the services that can minimize parental stress is implementation of family centered care. The objective of this research is to know the relationship between the implementation of family centered care by nurse with parental stress during infant’s hospitalization in Perinatology Ward Panembahan Senopati Hospital, Bantul,Yogyakarta.This research was a non-experimental, with a cross-sectional design. The sampling technique was purposive sampling with a total of 95 respondents whose parents were hospitalized in the Perinatology Ward of Panembahan Senopati Hospital, Bantul, Yogyakarta. Data was perfomed by kendall tau test. Family centered care application carried out by nurses in the Perinatology Ward of Panembahan Senopati Hospital Bantul, Yogyakarta, was in the majority in the good category of 45 respondents (47.4%), and the stress experienced by parents in the low stress category was 44 respondents (46.3%). Correlation test results p-value = 0.000 (p-value 0.05)and r = 0.899.The conclussion was there was a relationship between the implementation of family centered care performed by nurses with parental stress during infant’s hospitalization. The better implementation of family centered care, the lower the stress level of parents.